(untitled) (Ingeniería, Sostenibilidad y Sociedad, 2022)
This project aims to develop an infrastructure for training and selling legal and personal traumatic weapons. Due to the current regional insecurity, it is necessary for citizens to have access to defense resources under strict training and professional supervision.